2011
DOI: 10.1007/s11255-011-0095-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between objectively assessed sleep disorders and inflammatory markers among kidney transplant recipients

Abstract: We did not find any association between the presence of objectively assessed sleep disorders and inflammatory markers in kidney transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 42 publications
1
18
2
Order By: Relevance
“…It must be recognized that several predominantly negative studies, finding no association between sleep and immune markers, have also been published. For example, one study found no elevations among patients with kidney disease 139. Another study by Taheri et al found no association between sleep and CRP,126 a negative finding that was also demonstrated by Haack et al79 Tuomilehto et al also found no association between sleep and both CRP and IL-6 in the context of a lifestyle intervention (which may have overshadowed any association) 140.…”
Section: Limitations Of Existing Studiesmentioning
confidence: 93%
“…It must be recognized that several predominantly negative studies, finding no association between sleep and immune markers, have also been published. For example, one study found no elevations among patients with kidney disease 139. Another study by Taheri et al found no association between sleep and CRP,126 a negative finding that was also demonstrated by Haack et al79 Tuomilehto et al also found no association between sleep and both CRP and IL-6 in the context of a lifestyle intervention (which may have overshadowed any association) 140.…”
Section: Limitations Of Existing Studiesmentioning
confidence: 93%
“…In contrast, Fornadi et al did not find any significant difference in TNF-α level in 100 randomly selected kidney transplant patients. 16 Several studies examined fibrinogen, an acute-phase reactant, in OSA patients. Although some studies showed increased levels in severe OSA, [17][18][19] others showed less straightforward results, without increase in fibrinogen or changes after continuous positive airway pressure (CPAP) treatment.…”
Section: Inflammatory Biomarkers Play a Key Role In The Pathogenesis mentioning
confidence: 99%
“…Recently, growing evidence shows that OSA is associated with renal disorders, especially chronic kidney disease (CKD) and end-stage renal disease (ESRD) [3][4][5][6][7][8]. Patients with impaired renal function, CKD, ESRD, even kidney transplantation, exhibit a high prevalence of OSA [3][4][5], and inversely, OSA is independently correlated with increased urinary albumin excretion and loss of kidney function [7,8].…”
Section: Introductionmentioning
confidence: 99%